(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Many academics criticize charity appeals that focus on negative emotions to drive donations. With UK citizens being statistically more likely to donate to save a dog’s life over a refugee’s life, understanding how emotions impact charitable giving may help non-profits match their marketing appeals to motivations of the donor. Consequently, this study examines the underlying motivations of individuals through public service motivation theory and investigates if it leads to donations when beneficiaries are dogs or refugees. Furthermore, we draw upon positive emotions to see if they influence the relation between motivation and donations. Using a vignette web-based survey, 328 respondents had the option to spend money on a dog rescue charity, a Syrian refugee charity or decide to withhold donations entirely. The study found a positive relation between public service motivation and monetary giving. However, the relations differed when individual public service motivation dimensions were taken into account across the two beneficiaries. When positive emotions were included in the moderation tests, results were contrary to what was expected. These findings suggest non-profit marketers target audiences with high levels of public service motivation, but that positive emotions may not be effective in generating donations.